Pertumbuhan dan Densitas Populasi Larva Hermetia illucens (L.) pada Media Tumbuh Limbah Nanas dan Dedak Padi - Cesaria Anggun Kinanty; Diah Wulandari Rousdy; Firman Saputra (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The presence of Hermetia illucens larvae in waste management systems is very beneficial because of their ability to degrade waste. The growth of Hermetia illucens larvae depends on the adequacy of nutrients contained in the growth media such as protein and fat. The purpose of this study was to determine the growth, density and nutritional correlation of pineapple and rice bran media on Hermetia illucens larvae. The study used a completely randomized design consisting of 5 treatments, namely: 1) 100% pineapple waste; 2) 75% pineapple waste and 25% rice bran; 3) 50% pineapple waste and 50% rice bran; 4) treatment of pineapple waste 25% rice bran 75%; and 5) 100% rice bran. Each treatment consisted of 5 replications. Hermetia illucens larvae were reared for 21 days in organic waste media. The results showed that Hermetia illucens larvae grew optimally on a combination of 75% pineapple waste and 25% rice bran, namely an average length of ±15.298 mm and an average weight of ±11.644 g (sig <0.05), while the population density of the larvae showed no significant difference between treatments. with a density of 0.023-0.024 fish/cm3. The results of Pearson correlation analysis showed that the nutrient content of the media such as protein, fat, ash, moisture content and crude fiber had an effect on the length and weight of Hermetia illucens larvae, but had no effect on the larval population density.